2014
DOI: 10.1371/journal.pone.0096058
|View full text |Cite|
|
Sign up to set email alerts
|

Characteristics of Bone Turnover in the Long Bone Metaphysis Fractured Patients with Normal or Low Bone Mineral Density (BMD)

Abstract: The incidence of osteoporotic fractures increases as our population ages. Until now, the exact biochemical processes that occur during the healing of metaphyseal fractures remain unclear. Diagnostic instruments that allow a dynamic insight into the fracture healing process are as yet unavailable. In the present matched pair analysis, we study the time course of the osteoanabolic markers bone specific alkaline phosphatase (BAP) and transforming growth factor β1 (TGFβ1), as well as the osteocatabolic markers cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 24 publications
2
24
0
1
Order By: Relevance
“…These results suggest that the FGF21‐associated decline in BMD during ageing might be attributable to a negative balance in bone turnover despite the increase in overall bone remodelling (Demontiero et al., 2012). Our findings are consistent with the increase in both BAP and TRAP5b concentrations, despite a decrease in BMD, in elderly men and women after hip replacement (Habermann, Eberhardt, Feld, Zichner, & Kurth, 2007), implying that bone remodelling and concentrations of bone turnover markers are likely to increase as a compensatory response to the declining BMD in older people (Wölfl et al., 2014).…”
Section: Discussionsupporting
confidence: 89%
“…These results suggest that the FGF21‐associated decline in BMD during ageing might be attributable to a negative balance in bone turnover despite the increase in overall bone remodelling (Demontiero et al., 2012). Our findings are consistent with the increase in both BAP and TRAP5b concentrations, despite a decrease in BMD, in elderly men and women after hip replacement (Habermann, Eberhardt, Feld, Zichner, & Kurth, 2007), implying that bone remodelling and concentrations of bone turnover markers are likely to increase as a compensatory response to the declining BMD in older people (Wölfl et al., 2014).…”
Section: Discussionsupporting
confidence: 89%
“…In addition, the osteoinductive potential of serum leptin showed possible activity in the SCI group and the control group at 16 weeks, which suggested that the positive eff ect of serum leptin on bone formation was related to the level of weight-bearing activities and normal adipose metabolism during fracture healing. Previous studies demonstrated that low BMD bone could be caused by disturbed metabolism of bone remodeling and led to a qualitatively reduced healing process [41]. Here, the same result was found in both control and SCI groups: higher BMD was correlated with better fracture formation.…”
Section: Discussionsupporting
confidence: 83%
“…Mallmin et al enrolled 16 patients with Colles' fracture and found a minor constant increase of osteocalcin of 1 ng/ml during the 16‐week follow‐up, comparable with our results during 3‐month follow‐up. Wolfl et al included 30 patients with metaphyseal fracture, 14 of them with Colles' fracture. They found CrossLaps increased in the bone of the normal BMD group constantly, whereas these levels decreased significantly in the bone of the group with low BMD from the first week.…”
Section: Discussionmentioning
confidence: 99%